Analysis of Grab Customer Satisfaction Levels in Makassar Based on Service Quality, Ease of Operation, and Promotional Strategy - Fajar Rakasiwi Syamsuddin (Economic: Journal Economic and Business, 2025)
This study investigates Grab customer satisfaction in Makassar based on service quality, ease of use, and promotions. The persistent issue of customer dissatisfaction, which may impact user loyalty, is addressed. The extent to which these elements contribute to user satisfaction is the objective of this study. A survey was conducted among all active Grab users in Makassar. A purposive sample of 150 individuals who had used Grab services at least five times in the past three months was selected. The influence of the independent variables on the dependent variable was measured through multiple linear regression data analysis. The results showed that service quality and ease of use had a positive and significant effect on customer satisfaction, and promotions also had a positive and significant effect on customer satisfaction.